The role of clinical pharmacology in enhanced recovery after surgery protocols: a comprehensive review (Anestezjologia Intensywna Terapia, 2020)
Clinical pharmacology has had an enormous impact in the development of anaesthesia practice. Improvement in drugs and the use of long-acting local anaesthetics in peripheral nerve blocks have reduced hospital stays and opioid consumption in both the hospital and ambulatory surgery settings. Ambulatory surgery centres are revolutionary because they provide an alternative to hospital-based outpatient services and generally provide favourable patient outcomes. Enhanced recovery after surgery (ERAS) was established in 2001 to improve patient care and increase the number of available ambulatory surgery centres. ERAS protocols arose out of the need to decrease physiological and psychological surgical stress with an emphasis on clinical pharmacology and recovery data. Overall, ERAS aims to reduce unfavourable sequelae, shorten the length of hospital stay, reduce costs, and improve patient recovery. Surgical subspecialties have embraced the philosophy of ERAS, creating unique protocols to meet their patients’ needs. There are ERAS guidelines available for nearly every specialty in healthcare, and ambulatory surgery is no exception. The goal of ERAS guidelines is to reduce patient recovery times and improve patient outcomes, with a heavy emphasis on clinical pharmacology data.